2000
DOI: 10.1164/ajrccm.162.2.9910059
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Enhances Chemical and Mechanical Sensitivities of Pulmonary C Fibers in the Rat

Abstract: It has been recently reported that pulmonary reflex responses to injection or inhalation challenge of capsaicin are enhanced by exogenous Prostaglandin E(2) (PGE(2)). The present study was carried out to determine whether PGE(2) enhances the stimulatory effects of chemical stimulants and lung inflation on vagal pulmonary C fibers, and if so, whether the excitabilities of other types of lung afferents are also augmented by PGE(2). In anesthetized, open-chest rats, administration of PGE(2) (1.5 microgram/kg/min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 26 publications
6
82
0
Order By: Relevance
“…In addition, PGE 2 infusion also significantly enhanced the C-fiber response to constantpressure lung inflation ( Figure 6). In contrast, the same dose of PGE 2 did not cause any detectable change in the sensitivity of either RARs or slowly adapting pulmonary stretch receptors to lung inflation (34).…”
Section: Excitability Of Airway Afferents Modulated By Inflammatory Mmentioning
confidence: 69%
“…In addition, PGE 2 infusion also significantly enhanced the C-fiber response to constantpressure lung inflation ( Figure 6). In contrast, the same dose of PGE 2 did not cause any detectable change in the sensitivity of either RARs or slowly adapting pulmonary stretch receptors to lung inflation (34).…”
Section: Excitability Of Airway Afferents Modulated By Inflammatory Mmentioning
confidence: 69%
“…
AbstractProstaglandin E 2 (PGE 2 ) is a prototypical inflammatory mediator that excites and sensitizes cell bodies (Kwong and Lee, 2002; and peripheral nerve terminals (Ho et al 2000) of primary vagal sensory neurons. Nearly all central nerve terminals of vagal afferents are in the nucleus tractus solitarius (NTS), where they operate with a high probability of release (Doyle and Andresen, 2001).
…”
mentioning
confidence: 99%
“…PGE 2 is known to induce airway hypersensitivity; for example, inhalation of aerosolized PGE 2 elicits cough and retrosternal soreness (Costello et al, 1985), and enhances the sensitivity of the cough reflex response to inhaled capsaicin in humans (Chaudry et al, 1989). Indeed, an earlier study in our lab has shown that PGE 2 can elevate the sensitivity of pulmonary C-fiber afferents (Ho et al, 2000). Studies in an isolated pulmonary nodose/jugular neuron preparation further revealed that the sensitizing effect involves the intracellular cAMP/PKA signaling pathway, which is presumably triggered by activation of EP 2 and EP 4 prostanoid receptors expressed in these neurons (Kwong and Lee, 2002;Gu et al, 2003).…”
Section: Introductionmentioning
confidence: 84%